American Society of Plastic Surgeons Member Post-Operative Opioid Prescribing Patterns. Issue 3 (March 2019) - Torabi, Radbeh; Bourn, Lynn; Mundinger, Gerhard S.; Saeg, Fouad; Patterson, Charles; Gimenez, Alejandro; Wisecarver, Ian; St. Hilaire, Hugo; Stalder, Mark; Tessler, Oren
Abstract : Introduction: Despite the widespread use of opioids in pain management, there are currently no evidence-based guidelines for the treatment of postoperative pain with opioids. Although other surgical specialties have begun researching their pain prescribing patterns, there has yet to be an investigation to unravel opioid prescribing patterns among plastic surgeons. Methods: Survey Monkey was used to sample the American Society of Plastic Surgeons (ASPS) members regarding their opioid prescribing practice patterns. The survey was sent randomly to 50% of ASPS members. Respondents were randomized to 1 of 3 different common elective procedures in plastic surgery: breast augmentation, breast reduction, and abdominoplasty. Results: Of the 5, 770 overall active ASPS members, 298 responses (12% response rate) were received with the following procedure randomization results: 106 for breast augmentation, 99 for breast reduction, and 95 for abdominoplasty. Overall, 80% (N = 240) of respondents used nonnarcotic adjuncts to manage postoperative pain, with 75.4% (N = 181) using nonnarcotics adjuncts >75% of the time. The most commonly prescribed narcotics were Hydrocodone with Acetaminophen (Lortab, Norco) and Oxycodone with Acetaminophen (Percocet, Oxycocet) at 42.5% (N = 116) and 38.1% (N = 104), respectively. The most common dosage was 5 mg (80.4%; N = 176), with 48.9% (N = 107) mostly dispensing 20–30 tablets, and the majority did not give refills (94.5%; N = 207). Conclusions: Overall, plastic surgeons seem to be in compliance with proposed American College of Surgeon's opioid prescription guidelines. However, there remains a lack of evidence regarding appropriate opioid prescribing patterns for plastic surgeons.